Pengabdian Masyarakat Cara Mengembangkan Potensi Daerah Menjadi Pariwisata Unggulan Di Desa Hariara Pohan - Irsyadiyah Al Marhindy; Romaulina Sumbayak; Rosita Manawari Girsang; Mahaitin H Sinaga; Yoan Hendrawan Junpridan Saragih (Universitas, 2022)
Entrepreneurship is a creative and innovative ability, keen to see opportunities and always open to any positive input and changes that can bring the business to continue to grow. Businesses should have value and be useful where this can be done through the application of the concept of social entrepreneurship. Various groups have begun to discuss the concept of social entrepreneurship as an innovative solution in solving social problems. The purpose of social entrepreneurship is the realization of social change in a better or positive direction and solving social problems for the benefit of the community